(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
A newly innovated UV-Pit-Light trap specific for trapping beetle species within oil palm plantations is described and the results of experiments on its efficacies that were carried out within different oil palm age stands are presented. The UV-Pit-Light trap is made of two parts: a lower located 1-L plastic collection container inserted into the ground, 6V fast recharging lead-acid battery and 4-W miniature UV-bulb attached to electronic device with wire clips, with the upper located plastic stool for the basic stand and the wide plastic basin for rain and light shield. The UV-Pit-Light trap caught significantly higher beetle specimens, which also included several morphospecies from the common beetle families found in oil palm plantations with 1.5 to 2 times higher in abundances including Nitidulidae, Curculionidae, Scarabaeidae, and Tenebrionidae. Rare beetle families of Aderidae, Cerambycidae, Histeridae, and Lagriidae, which not to be found in passive pitfall trap, were caught in considerable abundances in the UV-Pit-Light trap. The short electro-magnetic wavelengths of UV-light source included many closely packed epigeal related micro-habitats, which makes the UV-Pit-Light trap specific for sampling beetles specifically related within micro-habitats of various oil palm age stand types. The use of only four units of UV-Pit-Light trap compared with 100 units of passive pitfall trap is adequate for sampling beetle species community which includes both the common and uncommon families, and include two times higher for the most abundant and common species than the passive pitfall trap. Thus, the UV-Pit-Light trap allows accurate and unbiased diversity and ecological evaluations of beetle species and proposed to be the specific trapping system for insect species dwelling within the epigeal related micro-habitats oil palm plantations.Â